2020
DOI: 10.3390/nu12010227
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Dietary Adaptations in Women With and Without Gestational Diabetes: Evidence From the Growing Up in New Zealand Study

Abstract: Diet is a cornerstone of the management of gestational diabetes (GDM). We investigated differences in dietary patterns and dietary adaptations among pregnant women with and without GDM participating in the Growing Up in New Zealand study. Presence of GDM was determined using coded clinical data and plasma glucose results meeting the New Zealand Society for the Study of Diabetes diagnostic criteria. Women answered a food frequency questionnaire and questions regarding dietary changes and information received du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 51 publications
(69 reference statements)
0
21
1
1
Order By: Relevance
“…Our findings provide new information about the dietary patterns of women with GDM in late pregnancy. Diet is the cornerstone in the management of women with GDM, yet few studies 46,47 have examined maternal dietary patterns in these women. A cohort study conducted in South Korea assessed dietary patterns via factor analysis using a 3-day food record, although the timing of dietary data collection was unclear 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings provide new information about the dietary patterns of women with GDM in late pregnancy. Diet is the cornerstone in the management of women with GDM, yet few studies 46,47 have examined maternal dietary patterns in these women. A cohort study conducted in South Korea assessed dietary patterns via factor analysis using a 3-day food record, although the timing of dietary data collection was unclear 47 .…”
Section: Discussionmentioning
confidence: 99%
“…While there are similarities between the 'carbohydrate and vegetable pattern' and 'western pattern' and our 'Mixed' and 'Junk' patterns, respectively, some diversity is to be expected from the www.nature.com/scientificreports/ differences across cultures and methodologies. A recent longitudinal cohort study assessed differences in dietary patterns between 280 women with GDM and 5104 without GDM in New Zealand from already established dietary patterns among the cohort 46,48 . The authors reported four dietary patterns via PCA and using FFQ in the third trimester of pregnancy: 'Junk, ' 'Traditional/White bread, ' 'Fusion Protein' and 'Health conscious' 46,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer Studie mit 5384 Frauen, erhielten 46,9 % der Teilnehmerinnen eine Ernährungsberatung, wenn sie vor ihrer pränatalen Untersuchung als Risikogruppe für Gestationsdiabetes identifiziert wurden [19]. Nur 6 % der Frauen, die im Laufe der Schwangerschaft die Diagnose Gestationsdiabetes entwickelten, erhielten eine Ernährungsberatung vor der Schwangerschaft [19]. Des Weiteren wird die mütterliche MD vor der Schwangerschaft mit einem geringeren Risiko für Gestationsdiabetes verbunden [20].…”
Section: Studien Mit Ernährungsberatungunclassified
“…These results suggest that current nutritional strategies to treat women with GDM are effective in promoting behavior change [ 33 ], even if the target of normoglycemia has not been routinely achieved yet. Further evidence that women diagnosed with GDM are amenable in making dietary changes come from the Growing Up in New Zealand Study paper by Lawrence and colleagues in this Special Issue [ 34 ]. In their cohort, women with GDM reported lower scores for consuming “junk” and “traditional/white bread” dietary patterns and a higher chance of having received dietary advice from a professional.…”
mentioning
confidence: 99%